Announced inspection report: safety and cleanliness of hospitals. Campbeltown Hospital, Cowal Community Hospital, Mid Argyll Community Hospital and Integrated Care Centre, NHS Highland, 17-19 July 2018. (2018) - Unknown
No abstract available